2006
DOI: 10.1207/s15516709cog0000_73
|View full text |Cite
|
Sign up to set email alerts
|

Phonotactics and Articulatory Coordination Interact in Phonology: Evidence from Nonnative Production

Abstract: A core area of phonology is the study of phonotactics, or how sounds are linearly combined. Recent cross-linguistic analyses have shown that the phonology determines not only phonotactics but also the articulatory coordination or timing of adjacent sounds. In this article, I explore how the relation between coordination and phonotactics affects speakers producing nonnative sequences. Recent experimental results (Davidson 2005, 2006) have shown that English speakers often repair unattested word-initial sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 48 publications
1
39
0
Order By: Relevance
“…One possibility is that, for stop-initial sequences, talkers adjust the timing between consonants at a phonological level. That is, consonant clusters are pulled apart in time, not because of low level motor error but as a way to avoid phonotactic violation (Davidson, 2006b;Gafos, 2002). In the context of the current modeling paradigm this could be tested by manipulating the k ipi parameter.…”
Section: [ ( ) T D $ F I G ]mentioning
confidence: 99%
“…One possibility is that, for stop-initial sequences, talkers adjust the timing between consonants at a phonological level. That is, consonant clusters are pulled apart in time, not because of low level motor error but as a way to avoid phonotactic violation (Davidson, 2006b;Gafos, 2002). In the context of the current modeling paradigm this could be tested by manipulating the k ipi parameter.…”
Section: [ ( ) T D $ F I G ]mentioning
confidence: 99%
“…A large body of experimental research indicates that onsets with large sonority clines are, indeed preferable (for reviews, see Berent et al, 2007;Berent et al, 2009; but c.f., Davidson, 2006aDavidson, , 2006bPeperkamp, 2007;Redford, 2008), but because such onsets also tend to be more frequent in language use, the precise source of such preferences-sonority or frequency-is difficult to ascertain. A recent series of experiments, however, demonstrated that speakers favor onsets with large sonority clines to those with smaller clines even when both types of onsets are unattested in their language (Berent et al, 2007;Berent et al, 2008;Berent et al, 2009;Berent, 2008).…”
Section: Sonority Restrictions As a Putative Output Universalmentioning
confidence: 99%
“…These nonnative clusters were chosen because they were most likely to induce errors that could be easily perceived by a listener (i.e., the experimenter) for whom the clusters are nonnative (Davidson, 2006a(Davidson, , 2006b). This consideration was critical for providing accurate online feedback to participants.…”
Section: Present Investigationmentioning
confidence: 99%